Leniency and Halo Bias in Industry-based Assessments of Student Competencies: A Critical, Sector-based Analysis - Wolf, Katharina (Routledge, 2015)
Industry placements are popular means to provide students with an opportunity to apply their skills, knowledge and experience in a ‘real world’ setting. Within this context, supervisor feedback allows educators to measure students’ performance beyond academic objectives, by benchmarking it against industry expectations. However, industry assessments appear to be frequently clouded and overwhelmingly positive by nature, which questions the reliability and validity of supervisors’ judgement of competencies. Supervisor bias has been paid much attention within the context of clinical placements, as well as within the domain of social work. However, the concept has been largely ignored within business education, despite the increasing emphasis on – and deep integration of – work-integrated learning in the business curriculum. This paper sets out to address this gap by examining variances in mark distribution and apparent leniency in the context of a final-year, compulsory placement unit, based on observations and data collected over nine semesters (n = 546). The focus of this study is on gaining an understanding of the reasons behind assessment bias and the pressures placed on industry assessors. The data indicate that different types of placement locations apply dissimilar standards when assessing student performance. The author identifies three statistically different placement types (small business, not-for-profit and professional), which influence the strength and risk of grader bias, hence ultimately the assessment outcome.